Clinical audit of current Helicobacter pylori treatment outcomes in Singapore - Tiing Leong Ang; Kim Wei Lim; Daphne Ang; Yu Jun Wong; Malcolm Tan; Andrew Siang Yih Wong (Singapore Medical Journal)
Introduction: H. pylori eradication reduces the risk of gastric malignancies and peptic ulcer disease. First-line therapies include 14-day PAC (proton pump inhibitor [PPI], amoxicillin, clarithromycin) and PBMT (PPI, bismuth, metronidazole, tetracycline). Second-line therapies include 14-day PBMT and PAL (PPI, amoxicillin, levofloxacin). This clinical audit examined current treatment outcomes in Singapore. Methods: Clinical data of H. pylori-positive patientswho underwent empirical first- and second-line eradication therapies from 1 January 2017 to 31 December 2018 were reviewed. Treatment success was determined by 13C urea breath test performed at least 4 weeks after treatment and 2 weeks off PPI. Results: A total of 963 patients (862 PAC, 36 PMC [PPI, metronidazole, clarithromycin], 18 PBMT, 13 PBAC [PAC with bismuth], 34 others) and 98 patients (62 PMBT, 15 PAL, 21 others) received first-and second-line therapies respectively. A 14-day treatment duration was appropriately prescribed for first- and second-line therapies in 65.2% and 82.7% of patients, respectively. First-line treatment success rates were noted for PAC (seven-day: 76.9%, ten-day: 88.3%, 14-day: 92.0%), PMC (seven-day: 0, ten-day: 75.0%, 14-day: 69.8%), PBMT (ten-day: 100%, 14-day: 87.5%) and PBAC (14-day: 100%). 14-day treatment was superior to seven-day treatment (90.8% vs. 71.4%; P = 0.028). PAC was superior to PMC (P < 0.001) but similar to PBMT (P = 0.518) and PBAC (P = 0.288) in 14-day therapies. 14-day second-line PAL and PBMT had similar efficacy (90.9% vs. 82.4%; P = 0.674). Conclusion: First-line empirical treatment using PAC, PBMT and PBAC for 14 days had similar efficacy. Success rates for second-line PBMT and PAL were similar.